MENINGKATKAN KEDISIPLINAN ANAK USIA 5-6 TAHUN DENGAN MENGGUNAKAN MEDIA BONEKA TANGAN DI PAUD ASSALAFIYAH - Hamiroh, Aam; Nasem, Nasem; Putri Hendrayana, Saniyya (Penerbit Lafadz Jaya, 2026)
The low level of discipline among children serves as the background for this study. The children were unable to follow classroom rules, such as leaving their seats without permission, joking during prayer, and not participating in learning activities in an orderly manner. The aim of this study is to improve the discipline of children aged 5–6 years at PAUD Assalafiyah Banyusari by using gand puppets as media. This study employed a classroom action research model by Kemmis and Mc. Taggart, which consists of four stages: planning, action, observation, and reflection. Data collection techniques included interviews, documentation, and observation, while data analysis was conducted using both qualitative and quantitative methods. The results showed that the use of hand puppet media was effective in improving children's discipline. Prior to the intervention, the level of discipline was 32.5%, categorized as Emerging (MB). After the first cycle, the discipline level increased to 56%, categorized as Developing as Expected (BSH). In the second cycle, it further increased to 82%, categorized as Very Well Developed (BSB). Based on the final score, the research was declared successful, having met the minimum mastery criteria of 80%.